E-ticketing system - Farah Nadiah, Roslan (Universiti Malaysia Perlis, 2008)
In this globalization era, one system has been created to facilitated train passenger to purchase online tickets. This system is called e-ticketing system where the processes of purchasing the train ticket are made by accessing the web page system. Passengers don‟t have to go to the train station to make a reservation or ticket cancellation. To make a reservation, passengers have to fill in the New Reservation form and click at the Continue button to make a payment. This system also has a process to delay payment which is Reserve Transaction where passenger can delay payment 24 hours before train departure. Ticket cancellation process can be done through this system, passenger only have to click on the Cancellation link and system will displayed all the reservation that has been made, passenger have to click on the reservation that they wish to cancel and click on Cancel button for confirmation. This system also contains the information of the passenger desired destinations and passengers can search for the train schedule and fare when accessing this system. The reservation may only be paid by Master Card and Visa credit card. Passengers only have to complete all the credit card information needed when fill in the registration form. When passenger purchasing the ticket, the system will automatically made a payment to the bank.